New species of Argythamnia (Euphorbiaceae) restricted to Seasonal Forest of Brazil, with morphological and phylogenetic support - Ornelas, Márcia Martins; Külkamp, Josimar; Santos, Francisco De Assis Ribeiro Dos; Carneiro-Torres, Daniela Santos (Phytotaxa, 2024)
Argythamnia (Acalyphoideae, Euphorbiaceae) is a monophyletic genus with approximately 70 species exclusive to the New World, distributed from the southern United States to Patagonia. The greatest diversity of the genus occurs in southern North America, Central America and the Caribbean. The distribution of the genus is strongly related to seasonally dry vegetation, mainly in Seasonally Dry Tropical Forests and Woodlands in the Neotropics. Based on morphological and phylogenetic data, here we describe the eleventh species of the genus for Brazil and the fourth for the state of Bahia, where the greatest diversity of the genus in the country is concentrated. We present a description, distribution map, illustration, table with the main diagnostic characters, preliminary conservation status, palynological data, as well as the phylogenetic position for the new species.